Internet Cafe Billing System Data Security Using RC4 Stream Cipher - Bobi Akbar (Bahasa Indonesia, 2020)
In data communication, against a data security method known as cryptography (Cryptography). Cryptography is a data security method that can be used to maintain data confidentiality, data authenticity or integrity, and the authenticity of the sender. This method is intended so that important information of a limited or confidential nature sent through public telecommunications facilities cannot be known or utilized by unauthorized parties. In this case, data security is also needed at the internet cafe (internet cafe). Warnet which is a place that provides Interconnection Networking that connects computers to form a network system that covers the whole world (global). Each cafe requires a billing system that is used to determine the state of the user in using the facilities at the cafe, starting from how long it takes to use and how much it costs each user. For this reason, so that the data on the billing system cannot be manipulated or modified by unauthorized persons, it is necessary to secure data. The data security method that will be used is cryptography, especially by using the RC4 stream cipher.